2022
DOI: 10.2147/idr.s348571
|View full text |Cite
|
Sign up to set email alerts
|

Nephrotoxicity and Efficacy Assessment of Polymyxin B Use in Renal Transplant Patients

Abstract: Purpose This study investigates the nephrotoxicity and efficacy assessment of polymyxin B (PMB) use in renal transplant patients. Patients and Methods This retrospective study included adult (>18 years of age) renal transplant patients who received PMB intravenous drip for more than 72 hours. Efficacy assessment of PMB included clinical treatment efficacy, microbiological efficacy at the end of PMB treatment, and in-hospital all-cause mortality. Nephrotoxicity of PMB wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
2
0
0
Order By: Relevance
“…29 (85.29%) patients were considered of clinical cure or improved. The clinical efficacy of polymyxin B in the current study was similar to the efficacy of polymyxin B in other transplant patients reported previously ( Mostardeiro et al, 2013 ; Wen et al, 2022 ). However, a relatively lower nephrotoxicity rate of polymyxin B (14.71%) was observed in our study compared to those reported in renal transplant patients, since kidney transplant patients are prone to renal dysfunction ( Mostardeiro et al, 2013 ; Wen et al, 2022 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…29 (85.29%) patients were considered of clinical cure or improved. The clinical efficacy of polymyxin B in the current study was similar to the efficacy of polymyxin B in other transplant patients reported previously ( Mostardeiro et al, 2013 ; Wen et al, 2022 ). However, a relatively lower nephrotoxicity rate of polymyxin B (14.71%) was observed in our study compared to those reported in renal transplant patients, since kidney transplant patients are prone to renal dysfunction ( Mostardeiro et al, 2013 ; Wen et al, 2022 ).…”
Section: Discussionsupporting
confidence: 90%
“…The clinical efficacy of polymyxin B in the current study was similar to the efficacy of polymyxin B in other transplant patients reported previously ( Mostardeiro et al, 2013 ; Wen et al, 2022 ). However, a relatively lower nephrotoxicity rate of polymyxin B (14.71%) was observed in our study compared to those reported in renal transplant patients, since kidney transplant patients are prone to renal dysfunction ( Mostardeiro et al, 2013 ; Wen et al, 2022 ). However, a recent study performed by Li et al (2021) in renal transplant patients showed an extremely low incidence of AKI, as they used a relatively lower maintenance dose of 40 mg q12h.…”
Section: Discussionsupporting
confidence: 90%